Acute contact toxicity of insecticides for the chemical control of the invasive yellow-legged hornet Vespa velutina nigrithorax (Hymenoptera: Vespidae) - Paula Malaquias Souto; Artur Sarmento; Nuno Capela; António Aguilar; Henrique M.V.S. Azevedo-Pereira; Cassiana Rebello Carvalho; Eric Darrouzet; Mélissa Haouzi; Luís António Henriques; Sara Leston; Fernando Ramos; José Paulo de Sousa (PLoS ONE, 2025)
The yellow-legged hornet, Vespa velutina subs. nigrithorax Buysson, 1905, originally from Southeast Asia, has become an invasive species in Europe since its introduction in France around 2004. Its rapid proliferation and voracious predatory behavior pose a significant threat to native insects, particularly honeybees and other pollinators, impacting agricultural production, biodiversity, and human safety. Eradication in Europe seems now impossible, and the control efforts are hindered by the lack of standardized application protocols, including for insecticide use, leading to potential indiscriminate pesticide application and, consequently, environmental damages. Our study evaluated the acute contact toxicity on V. v. nigrithorax workers of four commercially available formulations containing acetamiprid, cypermethrin, a mix of natural pyrethrins, and Spinosad as active ingredients. These tests were performed in laboratory conditions, offering novel data for the chemical control of this invasive species. Our results suggest acetamiprid and spinosad as promising candidates for the yellow-legged hornet control. Further research is needed to validate their efficacy under field conditions and assess ecological impacts of these pesticides on non-target organisms. Integrated pest management strategies should prioritize insecticides with low non-target toxicity and minimal environmental persistence to mitigate resistance development and ensure effective pest control. Comprehensive assessments considering multiple factors beyond mortality are essential for informing sustainable pest control strategies.